Changing Spatial Concentration of Sectoral Employment in China's Pearl River Delta 1990–2005. (1st October 2012) - Cheng, Fangfang; Boerboom, Luc; Geertman, Stan; Hooimeijer, Pieter
ABSTRACT Using county‐level employment data, we analyse how the spatial concentration of jobs has changed in China's Pearl River Delta (PRD) between 1990 and 2005. Despite unique Chinese policies that exhibit strong influence on the economic landscape, we detect key parallels with the patterns found in classic theories and empirical studies in Western contexts. Total employment has become increasingly concentrated. This aggregate picture hides important sectoral variations though: manufacturing employment has spread out to suburban areas; producer service jobs have increasingly concentrated in metropolitan centres; and consumer and public services have clustered in areas with high aggregate population. We argue that the major forces that are shaping the economic landscape in PRD are the market institutions and development path‐dependency. Under the circumstances of an increasingly liberalised market and decentralised government, policy now may function as a dynamic tool to magnify local spatial‐economic and historical advantages and to balance uneven regional development.